Laparoscopic management of benign gastric outlet obstruction: a case series with review of literature - Nagula, Mounish R.; Joshi, Abhijit S. (International Surgery Journal, 2024)
Surgery for peptic ulcer disease has since long become a thing of the past, in the era of proton pump inhibitors. Today, it is difficult to believe that these were common operations about 6-7 decades ago. Such has been the impact of proton pump inhibitors (PPI), that, surgery for peptic ulcer has been relegated to the realms of history. However, even in present day, in some rare clinical situations, surgeons may have to resort to surgery for patients suffering from peptic ulcer disease. Herein, we present our experience of laparoscopic surgical management of one of those rare clinical scenarios related to severe peptic ulcer disease. The clinical condition in discussion is gastric outlet obstruction caused by severe peptic ulcer disease in the first part of duodenum. We identified 8 patients (7 males and 1 female) who underwent laparoscopic vagotomy with gastrojejunostomy for benign gastric outlet obstruction, at our institution, operated upon by a single surgeon, between 2004 to 2023. All patients had undergone oesophago-gastro-duodenoscopy (OGD scopy), and contrast enhanced computerised tomography (CECT) of the abdomen. The patients were analysed for age, sex, symptoms, pre-operative evaluation, morbidity/mortality and functional outcomes. They were also reviewed to examine the length of stay, length of procedure, complications and recurrent symptoms on follow-up.